2018
DOI: 10.1007/s10903-018-0766-x
|View full text |Cite
|
Sign up to set email alerts
|

Visual Health and Visual Healthcare Access in Refugees and Displaced Persons: A Systematic Review

Abstract: Vision impairment is a significant global health concern. Still, there remains a gap in our knowledge of visual health in refugees. We conducted a systematic review of the distinctive eye care needs of refugees. We screened PubMed, EMBASE, and Web of Science through February 17, 2017 for studies that focused primarily on visual health in refugees. Risk of bias was assessed using the National Heart, Lung, and Blood Institute quality assessment tools. 26 studies were included in the final review. The prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“… 33 A systematic review in refugee populations worldwide also found a high prevalence of visual impairment and refractive error. 34 …”
Section: Discussionmentioning
confidence: 99%
“… 33 A systematic review in refugee populations worldwide also found a high prevalence of visual impairment and refractive error. 34 …”
Section: Discussionmentioning
confidence: 99%
“…myopia generally reported in economically deprived settings [20] and may also indicate a higher prevalence of other, nonrefractive ocular conditions such as infections [21,22], which have been documented in the Rohingya camps. The existing literature on visual health among displaced populations, including a recent review [11], has documented high prevalence of blindness [12,[22][23][24][25] in these communities, ranging from 1.3% to 26.2% [11]. However, few published studies [26][27][28][29] have focused on the delivery of eye care services rather than simply assessing the existing burden, and none of these have measured the demand for comprehensive eye care service in a defined refugee community, beyond a single disease focus such as refractive error [27][28] or trachoma [29].…”
Section: Plos Medicinementioning
confidence: 99%
“…However, these initiatives have largely focused on the needs of settled populations. A growing body of information exists about the visual health and unique eye care needs of displaced people [11,12], and there is increasing awareness of the unmet need for vision care in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that the prevalence of vision impairments and blindness among refugees are common and often higher than the general population. A recent systematic review found that the prevalence of blindness in the refugee camps can range from 1.3% to 26.2% [11]. A study with Afghan refugees in Pakistan revealed that 2.1% of all refugees there were blind, and 6.9% were visually impaired [12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the major interventions, in most places, including refugee camps, to control childhood blindness are public health in nature (vitamin A supplementation and measles immunisation) [14]. However, the need for eye care interventions for refugees are unique, and in every stage of displacement, such interventions should be targeted [11].…”
Section: Introductionmentioning
confidence: 99%